Investigation of synergic activity of ceftazidime and colistin, and the effect of baicalin on biofilms - Biyik, İlknur; Tanriverdi Çayci, Yeliz; Birinci, Asuman (The Journal of Infection in Developing Countries, 2025)
Introduction: The objectives of this study were to determine the rates of biofilm formation by Pseudomonas aeruginosa (n: 136) isolates from different samples collected from intensive care patients; and to determine the synergistic effects of the combination of ceftazidime and colistin, and the inhibitory effect of baicalin on biofilm formation in strong biofilm-producing bacteria (3+). Methodology: Previous studies have performed biofilm grading based on microplate absorbance measurement to phenotype the biofilm formation rate. The in vitro synergistic efficacy of the combination of colistin and ceftazidime was evaluated using the checkerboard method for strains with 3+ biofilm test results. In addition, sub-minimum inhibitory concentration (sub-MIC; MIC/2, MIC/4, MIC/8) values of the biofilm inhibitory effect of baicalin were determined. Results: The biofilm microplate method identified 5.15% of the isolates producing strong (3+) biofilms. Baicalin inhibited biofilm formation by 67.00–90.64% at sub-MIC concentration of 512 µg/mL, in 7 strong biofilm-producing isolates. These findings suggest that baicalin is a potential adjunctive therapy for disrupting biofilms, although the combination of ceftazidime and colistin may not be effective in this context. Conclusions: No synergistic effect of ceftazidime and colistin antibiotics was detected in high biofilm-producing P. aeruginosa isolates from an intensive care unit, and it was determined that certain concentrations of baicalin were effective in biofilm formation.